Value-Addition of Cottonseed: Protein Extraction, Functional Characterization and its Application - KUMAR, MANOJ; POTKULE, JAYASHREE; SAXENA, SUJATA; PATIL, P. G. (Cotton Research Journal, 2021)
The use of each and every part of any crop leads to additional income to the farmer and at the same time reduces the environmental burden caused by inefficient use of the by-product. Cotton is grown in over 80 countries and it is an important cash crop in India. India is leading country in production and total cultivable area under cotton crop. It is mainly cultivated for fiber which is main economic part of the crop, however its by-products namely seeds, stalks, hulls can be utilized for production of value-added products. Cottonseed is one of the important by-products which contributes to 2/3 part of seed cotton. After oil extraction, the left over cottonseed cake/meal has 45-55% of protein. This protein if extracted efficiently can be utilized in food, feed or other non-edible functions. The current review provides insights on protein extraction techniques, functional characterization of the protein and various edible and non-edible applications of the protein. The diversified uses of cottonseed proteins in food supplements needs further study.